Acetylation & Co: an expanding repertoire of histone acylations regulates chromatin and transcription. Issue 1 (2nd April 2019) - Barnes, Claire E.; English, David M.; Cowley, Shaun M.
Abstract : Packaging the long and fragile genomes of eukaryotic species into nucleosomes is all well and good, but how do cells gain access to the DNA again after it has been bundled away? The solution, in every species from yeast to man, is to post-translationally modify histones, altering their chemical properties to either relax the chromatin, label it for remodelling or make it more compact still. Histones are subject to a myriad of modifications: acetylation, methylation, phosphorylation, ubiquitination etc. This review focuses on histone acylations, a diverse group of modifications which occur on the ε-amino group of Lysine residues and includes the well-characterised Lysine acetylation. Over the last 50 years, histone acetylation has been extensively characterised, with the discovery of histone acetyltransferases (HATs) and histone deacetylases (HDACs), and global mapping experiments, revealing an association of hyperacetylated histones with accessible, transcriptionally active chromatin. More recently, there has been an explosion in the number of unique short chain 'acylations' identified by MS, including: propionylation, butyrylation, crotonylation, succinylation, malonylation and 2-hydroxyisobutyrylation. These novel modifications add a range of chemical environments to histones, and similar to acetylation, appear to accumulate at transcriptional start sites and correlate with gene activity.